Conceptions on topological transitivity in products and symmetric products II - Rojas Carrasco, Anahí; Kantún Montiel, Aura Lucina; Méndez Alcocer, José Nobel; Méndez Salinas, Víctor Manuel (Glasnik Matematicki, 2024)
We continue the work initiated by A. Rojas, F. Barragán and S. Macías in Conceptions on topological transitivity in products and symmetric products. Thurk. J. Math. 44 (2020), 491–523. We consider classes of functions not included in the mentioned paper, namely: exact in the sense of Akin-Auslander-Nagar, fully exact, strongly transitive in the sense of Akin-Auslander-Nagar, very strongly transitive, exact transitive, strongly exact transitive and strongly product transitive.
Keywords: Transitividad topológica; Productos simétricos; Sistemas dinámicos